Congenital microvillus atrophy in a 4-month-old girl - (:unkn) unknown (TURKISH J PEDIATRICS, 1999)
Congenital microvillus atrophy is a severe generalized enteropathy with ultrastructural abnormalities of the intestinal brush border. It is a rather new clinicopathological entity which needs to be differentiated from other enteropathies within the spectrum of intractable diarrhea of infancy. The presented case was a four-month-old girl with a chronic, intractable diarrhea, beginning at birth. The diagnosis was established only after the electron microscopic examination of small intestinal mucosa which revealed the characteristic features of the disease. Congenital microvillus atrophy is a rare autosomal recessively inherited disorder and bowel transplantation becomes a realistic option of treatment. Therefore, it should be specifically considered in the differential diagnosis of chronic intractable diarrhea of infancy.
Keywords: congenital microvillus atrophy; intractable diarrhea; infant; INCLUSION DISEASE; TRANSPLANTATION; DIARRHEA; ENTITY